A screening assessment of the impact of sedimentological heterogeneity on CO2 migration and stratigraphic-baffling potential: Johansen and Cook formations, Northern Lights project, offshore Norway. (October 2022) - Jackson, William A.; Hampson, Gary J.; Jacquemyn, Carl; Jackson, Matthew D.; Petrovskyy, Dmytro; Geiger, Sebastian; Machado Silva, Julio D.; Judice, Sicilia; Rahman, Fazilatur; Costa Sousa, Mario
Highlights: Johansen-Cook storage unit consists predominantly of wave-dominated deltaic sandstones. Novel method used to screen impact of sedimentological heterogeneity on CO2 migration and stratigraphic-baffling potential. Screening method combines experimental design, sketch-based reservoir modelling and single-phase flow diagnostics. Multiple types of sedimentological heterogeneity have significant effects. Abstract: We use a method combining experimental design, sketch-based reservoir modelling, and single-phase flow diagnostics to rapidly screen the impact of sedimentological heterogeneities that constitute baffles and barriers to CO2 migration in the Johansen and Cook formations at the Northern Lights CO2 storage site. The types and spatial organisation of sedimentological heterogeneities in the wave-dominated deltaic sandstones of the Johansen-Cook storage unit are constrained using core data from the 31/5-7 (Eos) well, previous interpretations of seismic data and regional well-log correlations, and outcrop and subsurface analogues. Delta planform geometry, clinoform dip, and facies-association interfingering extent along clinoforms control: (1) the distribution and connectivity of high-permeability medial and proximal delta-front sandstones, (2) effective horizontal and vertical permeability characteristics of the storage unit, and (3) pore volumes injected at breakthrough time (which approximates the efficiency of stratigraphic baffling). In addition, the lateral continuity of carbonate-cemented concretionary layers along transgressive surfaces impacts effective vertical permeability, and bioturbation intensity impacts effective horizontal and vertical permeability. The combined effects of these and other heterogeneities are also influential. Our results suggest that the baffling effect on CO2 migration and retention of sedimentological heterogeneity is an important precursor for later capillary, dissolution and mineral trapping.